Sintesis Carbon Dots (CDs) Berfluoresensi untuk Bioimaging dengan Metode Ablasi Laser. - Jumardin Jumardin; Akhiruddin Maddu; Kokoeh Santoso; Isnaeni Isnaeni (Universitas Andalas, 2023)
Carbon Dots (CDs) were synthesized using laser ablation by focusing the laser beam on carbon (Tea) material in colloid (CH3) for 3 hours. UV-Vis spectroscopic and fluorometric characterization showed absorption of the wavelength peaks caused by the control treatment and after laser ablation and coating using Poly Ethylene Glycol (PEG400). The excitation and emission energies are formulations of CDs absorbance wavelength and fluorescence intensity. The absorbance coefficient is obtained based on the absorbance value of the cuvette thickness. The transmittance value (T) is obtained based on the absorption coefficient multiplied by 100%. CD fluorescence wavelength based on control parameters was 489 nm. After laser ablation was 496 nm, and after coating was 511 nm. CDs morphology and size characteristics are 4 nm to 10 nm based on TEM measurements. Fluorescence analysis for bioimaging applications on the luminescence intensity value of internalized blue CDs in zebrafish eye organs. The average intensity of CDs in the eye organs, gill, intestinal, dorsal, and tail injection points was 88.15 %, 91.58 %, 92.76 %, and 0.00 %.